Complete architecture of integrated photonic circuits based on AND and NOT logic gates of exciton polaritons in semiconductor microcavities - Espinosa-Ortega, Tania (2013)
We present a complete photonic logic gate architecture in a compact solid-state system, making use of the nonlinear and spintronic properties of exciton polaritons in semiconductor microcavities. The dynamics of the system is modeled using the spinor Gross-Pitaevskii equations, and it is shown that the proposal fulfills all the necessary criteria for fully functioning information processing devices without the use of any external electric fields.